Conodont geothermometry of the lower Paleozoic from the Precordillera (Cuyania terrane), northwestern Argentina - Voldman, Gustavo Gabriel (2010)
The thermal history of the Precordillera terrane of northwestern Argentina has been constrained by the conodont colour alteration index (CAI) in combination with previously published paleothermal data (e.g., illite crystallinity and clay mineral assemblages). The pattern of paleotemperatures displays an increase in paleotemperatures to the west and south of the basin. This configuration shows a gradual and continuous transition from diagenesis to low-grade metamorphism, which is apparently not controlled by any of the morpho-structural subdivisions of the Precordillera (i.e., Western, Central, or Eastern). According to our results, the lower Paleozoic sedimentary burial played a secondary role in the heating of the Precordillera. Instead, the predominant component was loading by thrust sheets, which reflects the effects of the Devonian collision of Chilenia, particularly, in the Western Precordillera. Conversely, our paleothermometric data from the easternmost exposures of the Precordillera do not evidence anomalies referable to any of the accretionary events that contributed to the early Paleozoic building of the southern proto-Andean margin of Gondwana. Instead, the expected thermally altered conodonts from the Cuyania accretion are represented by metamorphosed conodont elements transported to the deeper settings of the west. The CAI data also suggest that overburden depth varied from ca. 3.6 km in the shelf region of the Eastern Precordillera to ca. 12 km in the slope to rise deposits of the Western Precordillera, thus providing constrains for the palinspastic restoration across the orogen. On the other hand, the smooth increase of peak paleotemperatures to the south of the Precordillera is associated with the exposure of deeper crustal levels at that sector, probably related to larger shortening due to stronger collisional effects, or alternatively, a weaker mechanical response of its elastic lithosphere.